Patients with tumour necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS) are hypersensitive to Toll-like receptor 9 stimulation. (22nd May 2019) - Negm, O H; Singh, S; Abduljabbar, W; Hamed, M R; Radford, P; McDermott, E M; Drewe, E; Fairclough, L; Todd, I; Tighe, P J
Summary: Tumour necrosis factor receptor-associated periodic syndrome (TRAPS) is a hereditary autoinflammatory disorder characterized by recurrent episodes of fever and inflammation. It is associated with autosomal dominant mutations in TNFRSF1A, which encodes tumour necrosis factor receptor 1 (TNF-R1). Our aim was to understand the influence of TRAPS mutations on the response to stimulation of the pattern recognition Toll-like receptor (TLR)-9. Peripheral blood mononuclear cells (PBMCs) and serum were isolated from TRAPS patients and healthy controls: serum levels of 15 proinflammatory cytokines were measured to assess the initial inflammatory status. Interleukin (IL)-1β, IL-6, IL-8, IL-17, IL-22, tumour necrosis factor (TNF)-α, vascular endothelial growth factor (VEGF), interferon (IFN)-γ, monocyte chemoattractant protein 1 (MCP-1) and transforming growth factor (TGF)-β were significantly elevated in TRAPS patients' sera, consistent with constitutive inflammation. Stimulation of PBMCs with TLR-9 ligand (ODN2006) triggered significantly greater up-regulation of proinflammatory signalling intermediates [TNF receptor-associated factor (TRAF 3), IL-1 receptor-associated kinase-like 2 (IRAK2), Toll interacting protein (TOLLIP), TRAF6, phosphorylated transforming growth factor-β-activated kinase 1 (pTAK), transforming growth factor-β-activated kinase-binding protein 2 (TAB2), phosphorylated TAK 2 (pTAB2), IFN-regulatory factor 7 (IRF7), receptor interacting protein (RIP), nuclear factor kappa B (NF-κB) p65, phosphorylated NF-κB p65 (pNF-κB p65) and mitogen-activated protein kinase kinase (MEK1/2)] in TRAPS patients' PBMCs. This up-regulation of proinflammatory signalling intermediates and raised serum cytokines occurred despite concurrent anakinra treatment and no overt clinical symptoms at time of sampling. These novel findings further demonstrate the wide-ranging nature of the dysregulation of innate immune responses underlying the pathology of TRAPS and highlights the need for novel pathway-specific therapeutic treatments for this disease. Graphical Abstract: